Complexos fosfínicos de Ru(II)/mercaptos contendo ligantes N,N-heterocíclicos: atividade citotóxica e mecanismo de ação - Oliveira, Leticia Pires de (Universidade Federal de São Carlos, 2022)
The main objectives of this study were the synthesis, characterization and biological studies of two series of ruthenium phosphine compounds containing different mercapto ligands, and contrasting in N,N-heterocyclic ligands in the coordination sphere. The series of compounds designated as series 1, consisted of seven compounds with general formula [Ru(NS)(dppb)(pyphen)]Cl (A1-A3) and [Ru(NS)(dppb)(pyphen)]PF6 (A4-A7), where dppb= 1,4’-bis(diphenylphosphine)butane; pyphen= 2-(pyren-1-yl)-1H-imidazo[4,5-f][1,10]phenanthroline; NS= 2-mercaptopyridine (pyS, A1 and A4), 2-mercaptothiazoline (tzdt, A2 and A5), 2-mercaptopyrimidine (pySm, A3 and A6), and 4,6-diamino-2-mercaptopyrimidine (damp, A7). The series 2, comprise three compounds, of general formula [Ru(NS)(dppb)(phen)]PF6 (A8-A10), where phen= 1,10-phenanthroline and NS (mercapto ligands)= pyS, tzdt and pySm. The precursor compound of Series 1, [RuCl2(dppb)(pyphen)], was characterized, and the results show that the compound probably presents conformational isomerism that is not verified on the free ligand or final complexes. The compounds of both series were analyzed by usual characterization techniques, such as elemental analyses, conductimetry, spectroscopic in the ultraviolet/visible and infrared, cyclic voltammetry, 1H, 13C{1H} and 31P{1H} nuclear magnetic resonance spectroscopy, and X-ray diffraction. The cytotoxic potential of compounds was evaluated against histologically distinct tumor lineages, MDA-MB-231 and MCF-7 (breast tumor lineages), A549 (lung adenocarcinoma tumor lineage), A2780 and A2780cis (ovarian tumor lineages), and against non-tumor lineages, MCF-10A (breast cell lineage) and MRC-5 (lung fibroblast cell line). This evaluation allows us to infer that the modification on the N,N-heterocyclic ligand resulted in smaller cytotoxic potential to compounds of series 1 than series 2. Despite this, the compounds of series 1 presented significant cytotoxicity in ovarian tumor cell lineages, exhibiting selectivity to this cell type, and a selectivity index of at least 2 with respect A2780cis and MRC-5 lines. The compounds of series 2 exhibited IC50 values significant, compared to the precursor and cisplatin, with similar activities between compounds to cell lines evaluated. Greater cytotoxic potential was displayed against MDA-MB-231 and A2780cis cell lineages, mainly complex A9 due its higher selectivity index. After analyzing the cytotoxic activity, the compounds were analyzed for possible interaction with biological targets, that can act how the stimulus triggers the cell death process or in the pharmacokinetics of compounds. All the complexes present reversible and weak interactions with DNA, mostly occurring in the minor groove of the biomolecule. The complexes were not capable alter the secondary and tertiary structure of DNA, therefore the interaction occurs weak and DNA is possibly not the determinant target to the compounds’ cytotoxicity. The compounds of Series 2 showed partial inhibition of the catalytic activity of the enzyme Topo IIα, while in the compounds of Serie 1 no inhibition of activity from this enzyme, which could be a way to justify the differential in cytotoxicity. Finally, the interaction with HSA showed that this protein can be associated with pharmacokinetics to the compounds, carrying them until the biological action site, with interaction through the Sudlow I site of human serum albumin protein. Studies with compounds A6 and A7 of Series 1, and A9 of Series 2, demonstrated the compounds could induce morphological changes that indicates cell death, the compounds exhibit cytostatic and cytotoxic effects on the cell lines analyzed, affect structures necessary for the metastatic cascade, and finally, exhibit apoptosis as cell death mechanism.
Ru(II) phosphine/mercaptos complexes containing N,N-heterocyclic ligands: cytotoxic activity and action mechanism
Keywords: Complexos de rutênio; Compostos citotóxicos; Ligantes N,N-heterocíclicos; Ligantes mercaptos; Compostos fosfínicos; Alvos biomoleculares; Ruthenium compounds; Cytotoxic compounds; N,N-heterocyclic ligands; Mercaptos ligands; Phosphinic compounds; Biomolecular targets; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA